Quality Attributes of Wheat and Aerial Yam Composite Flours and Evaluation of Biscuits from the Flours - Kayode, Rowland Monday-Ojo; Olowoseye, Adesewa Priscilla; Chia, Cynthia Nguevese; Adepeju, Adefisola Bola; Joshua, Victoria Auhoiza (Food Science and Engineering, 2024)
Wheat flour is the basic flour for flour confectionaries; however, its strict agronomic requirements limit its cultivation in many regions of the world. Hence, it has to be imported, raising the cost of production. Researchers are on the lookout for cheaper alternatives from locally available materials, and this has led to the use of composite flours. This study aimed to evaluate the quality attributes of wheat and aerial yam composite flours and the properties of biscuits produced from the composite flours. The composite flours were analyzed for their functional, proximate, mineral and phytochemical properties. While the biscuits were evaluated for their physical, microbial and sensory properties. Results showed a significant increase in the protein, fibre and fat contents of the composite flour in comparison to the control with values ranging from 5.77-7.18%, 0.4-0.62%, and 3.4-3.62%, respectively. Calcium (1.16-1.69 mg/100 g), iron (0.38-0.67 mg/100 g), magnesium (24.00-35.38 mg/100 g), potassium (2.87-5.06 mg/100 g), sodium (0.20-0.28 mg/100g) and phytochemicals were also observed to increase in the composite flours. The composite flours also had lesser bulk densities (0.70-0.75 g/ml) and higher water absorption capacities (113.50-134.00 g/ml) than 100% wheat flour (0.77 g/ml and 102.50 g/ml, respectively). The physical and sensory properties of the biscuits produced from the composite flours compared favourably with those produced from the control flour as there was no significant difference in the diameter, taste, crispness and overall acceptability of the biscuits. The findings showed the suitability of aerial yam flour as an alternative to wheat flour.